Draft genome of ochrobactrum intermedium strain M86 isolated from non-ulcer dyspeptic individual from India - Kulkarni, Girish; Dhotre, Dhiraj; Dharne, Mahesh S.; Shetty, Sudarshan; Chowdhury, Somak; Misra, Vatsala; Misra, Sriprakash; Patole, Milind; Shouche, Yogesh (GUT Pathogens, 2013)
Background: Ochrobactrum intermedium is an emerging opportunistic pathogen of humans that is closely related to members of the genus Brucella. Earlier, we reported the case of an Indian subject with non-ulcer dyspeptic symptoms whose urease positive gastric biopsy revealed the presence of Helicobacter pylori along with non-Helicobacter like bacteria, eventually cultured and identified as O. intermedium strain M86. Results: Here, we describe the unclosed draft genome of the strain M86 with a length of 5,188,688 bp and mean G+C content of 57.9%. We have also identified many putative gene clusters that might be responsible for its persistence in the gastric mucosa. Comparative analysis of genomic features of Ochrobactrum intermedium strain M86 and Ochrobactrum intermedium LMG 3301(T) was also done. Conclusions: This paper attempts to gain whole-genome based insights into the putative gene determinants of O. intermedium for survival in the highly acidic stomach lumen environment. Identification of genes putatively involved in the various metabolic pathways may lead to a better understanding of the survival of O. intermdedium in acidic condition.

Detection of clostridium tetani in human clinical samples using tetX specific primers targeting the neurotoxin - Ganesh, Madhu; Sheikh, Nasira K.; Shah, Pooja; Mehetre, Gajanan T.; Dharne, Mahesh S.; Nagoba, Basavraj S. (Journal of Infection and Public Health, 2016)
Tetanus resulting from ear injury remains an important health problem, particularly in the developing world. We report the successful detection of Clostridium tetani using tetX specific primers targeting the Cl. tetani neurotoxin. The sample was obtained from an ear discharge of a case of otogenic tetanus in a 2-year-old male child. Based on the culture results of the ear discharge, Gram staining and virulence testing by genotyping, a diagnosis of tetanus was confirmed. This is the first report from India on the successful detection of Cl. tetani in a human clinical sample using tetX specific primers targeting the Cl. tetani neurotoxin. (C) 2015 King Saud Bin Abdulaziz University for Health Sciences. Published by Elsevier Limited. All rights reserved.
Keywords: Cl. tetani; Neurotoxin; Otogenic tetanus; Trismus

Deciphering taxonomic and functional diversity of fungi as potential bioindicators within confluence stretch of Ganges and Yamuna Rivers, impacted by anthropogenic activities - Samson, Rachel; Rajput, Vinay; Shah, Manan; Yadav, Rakeshkumar; Sarode, Priyanka; Dastager, Syed G.; Dharne, Mahesh S.; Khairnar, Krishna (Chemosphere, 2020)
<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">River confluences are interesting ecological niche with limited information in respect of the structure and the functions of diverse microbial communities. Fungi are gaining global attention as promising biological spectacles for defining the trophic status of riverine systems. We condense existing knowledge in confluence diversity in two Indian rivers (i.e. Ganges and Yamuna), by combining sediment metagenomics using long read aided MinION nanopore sequencing. A total of 63 OTU’s were observed, of which top 20 OTU’s were considered based on relative abundance of each OTU at a particular location. Fungal genera such as <em style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Aspergillus, Penicillium<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">, <em style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Kluveromyces, Lodderomyces,<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> and <em style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">Nakaseomyces<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> were deciphered as potential bio indicators of river pollution and eutrophication in the confluent zone. <em style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;">In silico<span style="color: rgb(46, 46, 46); font-family: NexusSerif, Georgia, "Times New Roman", Times, STIXGeneral, "Cambria Math", "Lucida Sans Unicode", "Microsoft Sans Serif", "Segoe UI Symbol", "Arial Unicode MS", serif; font-size: 18px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400;"> functional gene analysis uncovered hits for neurodegenerative diseases and xenobiotic degradation potential, supporting bioindication of river pollution in wake of anthropogenic intervention.